Chemistry of crop protection : (Wiley-VCH, 2003)
This book includes thirty invited lectures held at the 10th IUPAC International Congress on the Chemistry of Crop Protection in August 2002. The presentations cover fundamental aspects of biology, chemistry, biochemistry and molecular biology of disease, weed and insect control agents, as well as economic issues, aspects in production, formulation and application, and recent regulatory developments in environmental and consumer protection.